Una comunità rurale toscana di antico regime - Marco, Bicchierai (Firenze University Press, 2006)
In a perspective of local history that combines problem analysis with a reconstruction accessible even to non-specialists, this book addresses the economy, society and institutions of a rural community of the Tuscan Apennines. The community of Raggiolo is portrayed over a long span of time ranging from the late centuries of the Middle Ages up to the end of the eighteenth century. We are thus offered a picture of the Casentino mountains which reveals - in the centuries-old intertwining of mountain economy, social equality, sharing of the management of the local administration and the goods belonging to the collectivity - one of the main reasons for the resistance to change which was to mark the end of the ancien regime.